New species and records of Dicraeus Loew, 1873 from China (Diptera: Chloropidae) - Liu, Xiaoyan; Yang, Ding; Nartshuk, Emilia P. (Zootaxa, 2019)
A review of the species of the genus Dicraeus from China is provided. The following five described species are new to science: D. crassispinus sp. n., D. curvus sp. n., D. dentatus sp. n., D. liupanshanensis sp. n. and D. minutidentatus sp. n. Four species, D. fuscipennis Kanmiya, D. malaisei Nartshuk, D. nartshukae Kanmiya and D. rossicus Stackelberg, are recorded from China for the first time. A key to the species of the Dicraeus from China is given.